Superprotonic conduction of intrinsically zwitterionic microporous polymers based on easy-to-make squaraine, croconaine and rhodizaine dyes. Issue 13 (14th June 2022) - Taylor, Dominic; Hu, Xuanhe; Wu, Can-Min; Tobin, John M.; Oriou, Zuzana; He, Jun; Xu, Zhengtao; Vilela, Filipe
Abstract : Porous organic polymers (POPs) have been prepared via a novel metal-free polycondensation between a tritopic indole-based monomer and squaric, croconic and rhodizonic acids. Abstract : Porous organic polymers (POPs) have been prepared via a novel metal free polycondensation between a tritopic indole-based monomer and squaric, croconic and rhodizonic acids. Each of the three POPs exhibited high BET surface areas (331–667 m 2 g −1 ) and zwitterionic structures. Impedance measurements revealed that the intrinsic POPs were relatively weak proton conductors, with a positive correlation between the density of oxo-groups and the proton conduction. Doping the materials with LiCl vastly improved the proton conductivity up to a value of 0.54 S cm −1 at 90 °C and 90% relative humidity.